"Perioperative Unfolding Case Study"—A Lesson in Quality and Safety. (27th July 2020) - Altmiller, Gerry
ABSTRACT: Unfolding case studies present the opportunity for learners to develop and improve their critical thinking and problem‐solving skills to deliver safe patient care. The structure of an unfolding case study actively engages learners to determine and customize nursing care based on the patient's changing situation. In addition, this type of case study supports development of knowledge, skills, and attitudes consistent with the Quality and Safety Education for Nurses (QSEN) competencies. During the student session at the AORN Global Surgical Conference & Expo 2019, the author gave attendees the opportunity to participate in the "Perioperative unfolding case study" that was framed in the QSEN competencies. Session evaluations indicated that participants found the process provided a thorough overview of perioperative nursing and emphasized safety‐focused initiatives that protect patients undergoing operative and other invasive procedures. This article offers an in‐depth discussion of the "Perioperative unfolding case study" and its implementation.